Reinforced soil bund as passive protection structures: the New Zealand experience - Ewe, E (Slope Stability 2020: 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Reinforced soil structures are well known for their excellent performance in resisting external loads such as seismic shaking. The superior performance over rigid structures is due to the very ductile behaviour of the structures as a result of relatively closely spaced soil reinforcement inclusions in soil. The ductility of these structures is utilised in the field of very high dynamic impact energy of rockfall with an aim to protect infrastructure. Back-to-back reinforced soil structures or bunds are constructed with layers of reinforcement and suitable facing units designed to resist dynamic impact energy. Full-scale impact trials have been carried out on these structures in Italy and simplified design charts have been developed from there. Several of these reinforced soil bunds have been designed and constructed in Christchurch following the 2011–12 earthquake and in Kaikoura after the 2016 earthquake. This paper details case studies of two of these structures across Christchurch and Kaikoura in the south island of New Zealand.
Keywords: reinforced soil structures; at source control; passive protection structures; rockfall protection; hazard mitigation